Airglow observations of nighttime medium‐scale traveling ionospheric disturbances from Yonaguni: Statistical characteristics and low‐latitude limit. Issue 11 (28th November 2014) - Lakshmi Narayanan, V.; Shiokawa, K.; Otsuka, Y.; Saito, S.
Abstract The characteristics of nighttime medium‐scale traveling ionospheric disturbance (MSTID) features observed over Yonaguni (24.5°N, 123.0°E; 19.3°N dip latitude), Japan are studied using all‐sky imaging of OI 630.0 nm airglow emission. The uniqueness of these observations is that the area observed by the imager covers the transition region between low to middle latitudes in the ionosphere. Typical low‐latitude limit of midlatitude‐type nighttime MSTIDs possessing phase front alignments along the northwest to the southeast occurs in this region. These MSTID features are rarely sighted at dip latitudes below 15°. We selected 2 year period for analysis in which 1 year corresponded to the solar minimum conditions and another year to the solar maximum conditions. The MSTIDs were observed to extend to farther lower latitudes during the solar minimum conditions than during the solar maximum periods. Their observed range of wavelengths, phase velocities, phase front alignment, and propagation directions are similar to those observed at typical midlatitude sites. However, on many occasions the phase fronts of the observed MSTIDs did not extend over the whole field of view of the imager indicating that some process inhibits their extension to further lower latitudes. Detailed investigation suggests that the poleward propagating enhancement of airglow intensity, probably associated with the midnight pressure bulge, causes the MSTID features to disappear when they reach lower latitudes later in the night. When the MSTIDs reach lower latitudes well before midnight, they are found to be inhibited by the equatorial ionization anomaly crest region.